Differential susceptibility to chronic social defeat stress relates to the number of Dnmt3a-immunoreactive neurons in the hippocampal dentate gyrus. (January 2015) - Hammels, Caroline; Prickaerts, Jos; Kenis, Gunter; Vanmierlo, Tim; Fischer, Maximilian; Steinbusch, Harry W.M.; van Os, Jim; van den Hove, Daniel L.A.; Rutten, Bart P.F.
Highlights: Dnmt3a type II cells are found brain regions involved in adult neurogenesis. High numbers of Dnmt3a type II cells showed double labeling with DCX or NeuN. Type II cell density was increased in resilient animals compared to control and susceptible animals. Type II cell density correlates with anti-depressive behavior. Abstract: The enzyme DNA methyltransferase 3a (Dnmt3a) is crucially involved in DNA methylation and recent studies have demonstrated that Dnmt3a is functionally involved in mediating and moderating the impact of environmental exposures on gene expression and behavior. Findings in rodents have suggested that DNA methylation is involved in regulating neuronal proliferation and differentiation. So far, it has been shown that chronic social defeat might influence neurogenesis, while susceptibility to social defeat stress is dependent on gene expression changes in the nucleus accumbens and the mesolimbic dopaminergic system. However, the role of Dnmt3a herein has not been fully characterized. Our earlier immunohistochemical work has revealed the existence of two types of Dnmt3a-immunoreactive cells in the mouse hippocampus, of which one represents a distinct type with intense Dnmt3a-immunoreactivity (Dnmt3a type II cells) co-localizing with a marker of recent proliferation. Based on this, we hypothesize that behavioral susceptibility to chronic social defeat stress is linked to (i) Dnmt3a protein levels in the nucleus accumbens and hippocampus, and (ii) to the density of Dnmt3a type II cells in the hippocampal dentate gyrus. While no differences were found in global levels of Dnmt3a protein expression in the nucleus accumbens and hippocampus, our stereological quantifications indicated a significantly increased density of Dnmt3a type II cells in the dentate gyrus of animals resilient to social defeat stress compared to susceptible and control animals. Further characterization of the Dnmt3a type II cells revealed that these cells were mostly doublecortin (25%) or NeuN (60%) immunopositive, thus defining them as immature and mature neurons. Moreover, negative associations between the density of Dnmt3a type II cells and indices of depressive-like behavior in the sucrose intake and forced swim test were found. These correlational data suggest that DNA methylation via Dnmt3a in the hippocampus co-regulates adaptivity of the behavioral response to chronic social defeat stress, and set the stage for further experimental studies testing a mediating role of Dnmt3a in experience-dependent plasticity, neurogenesis and (mal) adaptation to severe stressors.